'The Kirk's Alarm': Burns and the Presbyterians in mid-Victorian Scotland. Issue 1 (March 2022) - Whatley, Christopher A.
Abstract : A preliminary exploration of the enduring impact of Burns's anti-clerical satires. In weakening the grip of more extreme Presbyterianism in Scotland Burns's contribution has not been fully appreciated. His role in this regard was one inspiration for the centenary celebrations of 1859. The poet's alleged immorality and personal example were viewed by clergymen and others as having contributed to the moral decline of Scottish society. Yet during the mid-Victorian era churchmen began to relent, and accepted that whatever his failings, Burns merited his status as the Nation's Bard.